The impact of preschool twins' physical difficulties on parental perceptions towards separation, closeness and friendship. Issue 4 (2nd April 2016) - Markodimitraki, Maria; Linardakis, Michalis; Kypriotaki, Maria; Manolitsis, George
Abstract : The aims of this study were to: (a) provide descriptive data of twins with physical difficulties among 120 Greek twins of preschool age; and (b) to investigate the impact of twins' health condition on parental perceptions towards twins' separation, closeness and friendship. The administration of School Policy for Twins and Higher Multiples Questionnaire to the parents of 60 twin pairs led to the following three-group sample based on twins' health condition: Group 1 consisted of pairs of healthy twins, Group 2 consisted of pairs of a healthy twin and a non-healthy co-twin and Group 3 consisted of pairs of non-healthy twins. The main results of this study are summarised as follows: (a) twins' health condition did not affect parents' preference to keep their twins together (school/home), rather than separate them; (b) twins' health condition affected twins' emotions towards separation; and (c) twins' health condition did not affect significantly twins' closeness and twins' preferences in friendship. This study attempts to advance investigation of the impact physical difficulties may have on parents' perceptions.